Kinetic Model for Drying in Frame of Generalized Fractional Derivatives - Ozarslan, Ramazan; Bas, Erdal (Mdpi, 2020)
In this article, the Lewis model was considered for the soybean drying process by new fractional differential operators to analyze the estimated time in 50 degrees C, 60 degrees C, 70 degrees C, and 80 degrees C. Moreover, we used dimension parameters for the physical meaning of these fractional models within generalized and Caputo fractional derivatives. Results obtained with generalized fractional derivatives were analyzed comparatively with the Caputo fractional, integer order derivatives and Page model for the soybean drying process. All results for fractional derivatives are discussed and compared in detail.
Keywords: drying kinetics; Lewis model; Caputo; generalized fractional derivative